IS MANUFACTURING COST AN OBJECTIVE CONCEPT? - LemKe, B. C. (The Accounting Review, 1951)
Abstract The justification for the adoption of standard cost should include the point that a proper or objective cost, however defined, can exist independent of subjective or incurred cost, at least temporarily. Standard cost for control purposes usually takes into account, or at least rationalizes, all expected expenditures and charges related to the manufacturing process. If competent factory engineers and superintendents are given a free hand in designing a factory for a stated rate of output of a product, there will be one combination of production factors which will be the most economical combination. Any deviation from this combination will yield a higher unit cost of output. Presumably the word objective can be used to describe such a unit cost. The isolation of this non-essential element from manufacturing cost, as ordinarily arrived at, might not be a difficult matter under all circumstances. If production is fairly standardized, it is likely that the rate of production is increased by exactly duplicating previously acquired combinations of factors of production, assuming stable conditions, and that it is decreased by ignoring similar combinations of factors of production.